DETERMINAN INFLASI DI INDONESIA PERIODE 1980-2015 - Risna Risna (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2016)
This study aims to determine the effect of government spending, the money supply, the interest rate of Bank Indonesia against inflation.This study uses secondary data. Secondary data were obtained directly from the Central Bureau of Statistics and Bank Indonesia. It can be said that there are factors affecting inflationas government spending, money supply, and interest rates BI. The reseach uses a quantitative approach to methods of e-views in the data. The results of analysis of three variables show that state spending significantand positive impact on inflationin Indonesia, the money supply significantand negative to inflationin Indonesia, BI rate a significantand positive impact on inflation in Indonesia